Prolonged Exposure Therapy in the Treatment of PTSD Based on Virtual Reality and Smartwatch Utilization: A Case Study in a Private Mental Health Clinic in Peru - Luyo, Rafael; Puican, Kurt; Wong, Lenis (Engineering, Technology & Applied Science Research, 2026)
Post-Traumatic Stress Disorder (PTSD) derived from sexual violence represents a critical public health challenge in Peru, where more than 42,000 cases were treated in 2022. Conventional therapies present limitations in recreating controlled exposure environments and objectifying clinical monitoring. This study presents Synapse, a platform that integrates Prolonged Exposure Therapy (PET) with immersive Virtual Reality (VR) and biometric monitoring via a smartwatch. The development comprised four phases: (i) PET selection through benchmarking, (ii) design of three therapeutic scenarios with progressive exposure levels, (iii) implementation of the environment in Unity, and (iv) development of a web application with cloud architecture. Validation was conducted in a private clinic in Lima with 30 patients diagnosed with PTSD, divided into a control group (traditional PET) and an experimental group (PET with Synapse), evaluated over three weekly sessions using Subjective Units of Distress (SUDS), heart rate (BPM), and the PCL-5 Scale. The results demonstrated the superiority of the experimental group with a 21.3% reduction in PCL-5 compared to 11.8% in the control group. Furthermore, the system evidenced greater initial emotional activation and superior reductions in anxiety, with more robust physiological habituation. The usability evaluation obtained 84.67 points on the System Usability Scale (SUS), classified as "Excellent". These findings establish that Synapse constitutes an effective tool to improve the efficacy of PET in PTSD, with great potential for implementation in public health systems.